Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja terhadap Kinerja Kru Kapal MV. Edwine Oldendroff 2020 - Ali Sulistyobudi; Moh. Hapit (Jurnal Pendidikan Manajemen Transportasi, 2024)
The Implementation of Work Safety and Health Management System on the Performance of ship’s crews at MV. Edwine Oldendorff’s Ship. 2022 Work safety and health at sea is very prioritized in the maritime world because it is one of the goals and indicators of a company's success and is a form of protection for workers. This study aims to conduct a research on occupational safety and health on the performance of ship’s crews at MV. Edwine Oldendorff. The data collecting by distributing questionnaires to 25 crew members on MV. Edwine Oldendorff and do some interview. The result shows that the relationship between work safety and employee performance had an influence of 38.7%. Similarly for the occupational health variable on employee performance has 36.4%. Work safety and occupational health on employee performance simultaneous implemented show an influence of 45.8%. The relationship between work safety, occupational health on employee performance both simultaneously has a strong relationship. Work safety and health of the performance of the crew at MV. Edwine Oldendorff has a higher influence of occupational safety and occupational health carried out simultaneously. The results of this study expect companies to improve occupational safety and health simultaneously, in order to get higher levels of achievement.